О европейском векторе развития университетских организаций: на пути к внедрению “европейской” модели? - Тарапатова, Н. (Социология: теория, методы, маркетинг, 2006)
The article deals with the analysis of the “European University” model. The problem of
transition from the so called “classical” model of university functioning (university as
“cultural institution”) to “managerial” (“entrepreneurial”) model of functioning is
considered. University organization as a constituent of national educational system is
evaluated as to its perspectives of development.